1999
DOI: 10.1159/000013509
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative Glomerulonephritis with Subendothelial Deposits (Type 1) Associated with Hepatitis G Virus Infection in a Renal Transplant Recipient

Abstract: Background: Infection with hepatitis B virus (HBV) or hepatitis C virus (HCV) is a well-known etiology for membranoproliferative glomerulonephritis (MPGN) with subendothelial deposits (MPGN type 1). Material and Methods: The newly discovered hepatitis G virus (HGV) is currently under active investigation. We report the first case of de novo MPGN type 1 associated with HGV infection in a young male renal transplant recipient who manifested glomerulonephritis (GN) with proteinuria 7 years after transplant, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…[43][44][45][46][47] Hepatitis C virus is perhaps the most frequently defined cause of membranoproliferative GN, membranous GN, or thrombotic microangiopathy disease in the graft, 46,48,49 although hepatitis G virus and other viruses may contribute. 45,50 Finally, immunosuppressive therapy itself may play a role: Cyclosporine may cause a spectrum of renal injury including FSGS, whereas sirolimus toxicity may lead to the appearance of FSGS independently or as a co-factor in patients with a genetic susceptibility to this disorder. 51,52 In concert with recent publications, the data reported here emphasize that PTGN is an important cause of graft loss in renal transplant recipients and is associated with a dramatic reduction in graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46][47] Hepatitis C virus is perhaps the most frequently defined cause of membranoproliferative GN, membranous GN, or thrombotic microangiopathy disease in the graft, 46,48,49 although hepatitis G virus and other viruses may contribute. 45,50 Finally, immunosuppressive therapy itself may play a role: Cyclosporine may cause a spectrum of renal injury including FSGS, whereas sirolimus toxicity may lead to the appearance of FSGS independently or as a co-factor in patients with a genetic susceptibility to this disorder. 51,52 In concert with recent publications, the data reported here emphasize that PTGN is an important cause of graft loss in renal transplant recipients and is associated with a dramatic reduction in graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…The latency of the virus in our cases may have been due to the use of lowdose immunosuppressive therapy. Berthoux et al (14) reported the rst case of de novo membranoproliferative glomerulonephritis type 1 associated with HGV infection in a young male RTx who manifested glomerulonephritis with proteinuria 7 years after transplant, and whose original disease was chronic obstructive pyelonephritis secondary to nephrolithiasis. It is not known whether TTV causes renal allograft rejection or not.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses are important in renal graft rejection, with cytomegalovirus (CMV) being the most important virus causing renal graft rejection (8)(9)(10)(11)(12)(13). Recently it was reported that hepatitis G virus (HGV) caused rejection in an RTx, leading to glomerulonephritis (14). Although hepatitis C virus (HCV) causes glomerulonephritis, it is uncertain whether it also causes graft rejection (15).…”
mentioning
confidence: 99%
“…Recently, hepatitis C virus infection has been increasingly implicated as a cause of type I MPGN, [19][20][21][22] and the association of type I MPGN with human immunodeficiency virus (HIV) or other viruses, such as Epstein-Barr virus, BK type polyoma virus, hepatitis G virus, or parvovirus B 19, have also been described in patients after renal transplantation. [23][24][25][26][27] Although serological tests for hepatitis C virus (HCV) antibody were negative in both cases, we did not test for HCV RNA and other viruses. Steroid-induced immunosuppressive state could have caused some of these viral infections and contributed to deterioration of renal pathology.…”
Section: Discussionmentioning
confidence: 99%